Intramuscular versus oral iron supplementation in patients on renal replacement therapy receiving erythropoietin - Thiruventhiran, T.; Ang, B.B.; Tan, S.Y. (Faculty of Medicine, University of Malaya, 1999)
Anaemia in patients on renal replacement therapy is a comrnon problem and response to treatment with erythropoietin may be iimited by functional iron deficiency. We recently studied prospectively for 22 weeks the effect of iron supplementation via intramuscular and oral vs intramuscular vs oral routes in 16 patients on chronic haemodialysis with renal anaemia treated with erythropoietin injections. The rise in haemoglobin was significant in all patients except those on intramuscular iron only. This study supports unconfirmed observations that oral iron supplenientation may be effective in patients with renal anaemia associated with functional iron deficiency.